The effect of personality traits on the intention to adopt M-Learning - Sanjebad, Nesa Nabipouru (2014)
Students need motivation to use mobile devices for educational aims, but it is required to analyze their motivation. However, students and lecturers have been motivated recently to use mobile devices for educational aim. Many things can affect student willing to improve Mobile learning which personality traits is one factor which can motivate students. Although M-Learning has many advantages and benefits that make individuals to accept and adopt it, it is required to realize the factors that formulate their behavior in favor of M-Learning. This study proposed a model that identifies effect of personality traits on the intention to adopt M-learning. The model used TAM and Big Five models for analyzing personality and adoption of students. In this study, survey was conducted among two faculties that used E-Learning in high and low stage. These faculties were Faculty of Computing (FC) and Faculty of Health Science and Biomedical Engineering (FHSBE). The result of study shows that three factors of personality which analyze by Big Five model was accepted and two external factors like Perceived Enjoyment and Computer Self- Efficacy from TAM model can have influence to adoption a new technology like Mobile learning . The study found Perceived Usefulness and Conscientiousness are the most factors that influence on students to adoption Mobile learning.